Решите неравенство:
(х-8)(2х-6)-(х-8)(х+1)=0

распишите , подробно.

mashasumashedsoziogw mashasumashedsoziogw    1   29.04.2021 10:40    0

Ответы
малика2071 малика2071  29.04.2021 10:50

(x-8)*(2x-6-x-1)=0

(x-8)*(x-6-1)=0

(x-8)*(x-7)=0

x-8 = 0

x-7 = 0

x1 = 8

x2 = 7

ПОКАЗАТЬ ОТВЕТЫ
vasviktor vasviktor  29.04.2021 10:50

Пошаговое объяснение:

(х-8)(2х-6)-(х-8)(х+1)=0

(х-8)((2х-6)-(х+1))=0

(х-8)(2х-6-х-1)=0

(х-8)(х-7)=0

Х-8=0 и х-7=0

Х=8 х=7

ответ : х1=7 х2=8

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика